HEPATOPROTECTIVE ACTIVITY OF METHANOLIC EXTRACT OF MELIA AZEDARACH. L ON WISTAR RATS - DR.A.SUMATHI (International Journal of Pharma and Bio Sciences, 2013)
The objective of the present study appraised the hepatoprotective activity of methanolic extract of Melia azedarach. L leaves on Wistar rats. The Methanolic extracts of Melia azedarach. L (200mg & 500mg/kg,b.w,p.o) was administered respectively to the animals which were treated with carbon tetrachloride. Its effects on biochemical parameters were compared with standard drug silymarin (100mg/kg,b.w p.o). Melia azedarach. L showed prominent reduction of serum enzymes-AST, ALT, ALP, TP & Bilirubin (Aspartate Transaminase, Alanine Transaminase, Alkaline Phosphatase, Total Protein & Total bilirubin) when compared to the control rats. The hepatoprotective effect of Melia azedarach. L was comparable with the standard drug Silymarin. It was confirmed through histopathological study. The effect of extracts 500mg/kg was almost equal to that of standard drug Silyymarin.